The Correlation Between Vocabulary Mastery and Translation Accuracy of Students at English Language as Foreign Application Standard (Elfast) Pare Kediri - Kulsum, Ummu (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2020)
Translation is one of important knowledge which has to be mastered by the language learners, especially English Learners. The English learners will need some English books to enrich their knowledge. By having a good translation, the learners can transfer the content of the book correctly. Mastering vocabulary is very important in doing translation. The translator cannot always depend on the lexical meaning which were provided in the dictionary. The translator have to find the equivalence meaning in the translation in order the readers can read the target language as like they read the original. There are two problem statements in this study. The first one is whether the more vocabulary students have, the more their translation accuracy or not. The second is how significant is the correlation between vocabulary mastery and translation accuracy of students translation class at English Language as Foreign Application standard at ELFAST Pare Kediri. Population of this research is a whole number of the students who join translation (practice) subject which consist of one class with only 17 students of 2015 academic year. The instruments that were used in this research are documentation and tests (vocabulary mastery test and translation accuracy test). The obtained data of tests was analyzed by using statistic corelation product moment formula. The result showed that the more vocabulary of students have, the more their translation accuracy; and there is a significant correlation between vocabulary mastery and translation accuracy of students translation class at English Language as Foreign Application standart (ELFAST) PARE KEDIRI with high interpretation either in significant level of 5% or 1%. It was proven by the result of the obtained data, rxy is greater than rtable (0,805>0,482 or 0,606). It can be drown a conclusion that the students’ translation accuracy is very much influence by the amount of vocabularies they have. So, if the students want to increase their translation accuracy, the first step that should be done is increasing their vocabulary mastery. Then, increase the other factors that can influence their translation accuracy, such as grammar or syntax, morphology, semantic, etc.